Corrigendum to “Sickle cell disease clinical phenotypes in Nigeria: A preliminary analysis of the Sickle Pan Africa Research Consortium Nigeria database” [Blood Cells, Molecules and Diseases (2020) - Isa, Hezekiah; Adegoke, Samuel; Madu, Anazoeze (Blood Cells, Molecules and Diseases, 2020)
No abstract
Keywords: Sickle cell disease; Ghana; University of Ghana; ACE: Genetic Medicine; WAGMC; Abdul-Aziz Hassan; Chinatu Ohiaeri; Reuben Chianumba